Choroidal microvascular dropout and its relationship to progression in primary open-angle and pseudoexfoliation glaucoma - Jimin Park; Youn Hye Jo; Kyung Rim Sung (BMC Ophthalmology)
Abstract Background To compare the longitudinal change of choroidal microvascular dropout (CMvD) and its relationship with glaucoma progression between primary open angle glaucoma (POAG) and pseudoexfoliation glaucoma (PXG). Methods The analysis included 114 eyes of 114 patients, with 57 POAG and 57 PXG eyes matched by age and visual field (VF) mean deviation (MD). The angular circumference (AC) of CMvD was measured using the en-face choroidal layer images of optical coherence tomography angiography at baseline and the final follow-up. Progression of CMvD was defined as an increase in AC beyond measurement variability (-3.85° to + 3.28°) or the appearance of new CMvD during follow-up. Glaucoma progression was determined by MD change rate. Results The prevalence of CMvD was significantly higher in POAG than in PXG eyes (68.4% vs. 43.9%, p = 0.008) at baseline. However, by the final visit, the difference in prevalence between the groups was not significant (68.4% vs. 56.1%, p = 0.178). During the study period, seven PXG eyes developed new CMvD. There was no significant difference in MD progression rate between the stable and progressed CMvD subgroups in POAG (–0.7 ± 0.8 dB/year vs. − 0.8 ± 0.5 dB/year, p = 0.715). In contrast, PXG eyes showed a significantly faster MD progression rate in the progressed CMvD subgroup than in those with stable CMvD subgroup (–0.4 ± 0.7 dB/year vs. − 1.2 ± 0.8 dB/year, p = 0.010). Conclusions The progression of CMvD was more frequently observed in PXG eyes than POAG eyes and showed association with faster VF progression in PXG eyes.